Analysis of Organizational Culture and Human Resource Development on Organizational Commitment with Motivation as a Mediating Variable at the Medan Belawan Primary Tax Service Office - Khaidir Ali; Hernawaty Hernawaty; Muhammda Isa Indrawan (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
Organizational commitment is an important factor in improving performance and service quality in public sector agencies, including the Medan Belawan Tax Office (KPP). High service demands, modernization of the taxation system, and the dynamics of the work environment require employees to have a strong commitment to the organization. This study aims to analyze the influence of organizational culture and human resource development on organizational commitment, as well as to examine the role of work motivation as a mediating variable at the Medan Belawan Tax Office. This study uses a quantitative approach with a census method of 100 civil servants. Primary data was collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results show that organizational culture and HRD have a positive and significant effect on organizational commitment and work motivation. In addition, work motivation was found to have a positive and significant effect on organizational commitment. The results of the indirect effect test showed that work motivation acts as a mediating variable that strengthens the effect of organizational culture and human resource development on organizational commitment. The research model was able to explain 61.7% of the variation in organizational commitment and 43.1% of the variation in work motivation. The findings of this study emphasize the importance of strengthening a conducive organizational culture, implementing sustainable human resource development programs, and increasing employee work motivation in order to strengthen organizational commitment. This study is expected to contribute theoretically to the development of public sector human resource management science and serve as a basis for practical consideration for the leadership of KPP Pratama Medan Belawan in formulating more effective human resource management policies.